Performance of low frequency magnetometers to non-sinusoidal magnetic fields - Cortés, C. A. (2013)
This paper presents the second part of a research work dealing with the performance assessment of commercially available magnetometers. The aim of the article is to continue a comparative study of a magnetometer set, but now using non-sinusoidal signals. Nineteen magnetometers were tested using signals with two and more frequency components; some features of the meters were investigated: fft, rms value, peak value and wave capture functions.